A autocomposição pelo oficial de justiça : celeridade e acesso à justiça na prestação jurisdicional - Folle, Ana Júlia Cecconello (2025)
This paper aims to analyze the role played by the Court Officer and his/her contribution to the provision of jurisdiction, especially with regard to the attribution of selfcomposition in civil proceedings. Through the deductive method, doctrines, legislation, scientific publications and news were analyzed. The work is part of the research line Constitutional Jurisdiction and Democracy. In this scenario, this paper dealt with who the Court Officer is in Brazil, making an analysis from the historical origin of the position and its evolution, its attributions and responsibilities, reaching the critical point of the difficulties faced by this server in his/her job, in order to demonstrate the essentiality of the Court Officer within the Judiciary. It also dealt with the principles that govern his/her performance and the performance of his/her functions. Finally, the institute of selfcomposition was addressed, which is an innovation brought to the functions of the Court Officer in art. 154, VI, of the CPC/2015 that aims to bring greater speed and guarantee more effective access to justice, analyzing its origin and applicability. Thus, it was found that the inclusion of the Court Officer in the self-composition of conflicts reinforces his position as an essential assistant of justice and contributes to the respect and guarantee of the fundamental right of access to justice. It was possible to confirm that the CPC/2015 brought great progress to the jurisdiction by including such attribution; however, it is necessary to train the servers as well as the elaboration of sub-legal norms that regulate the practice of the activity.